Evaluating Action of Homoeopathy by using Gastrointestinal Symptom Rating Scale (GSRS) in Gastro Intestinal Disorders- A Case Series (Advancements in Homeopathic Research, 2022)
Gastrointestinal disorders are the one of the attention  seeking conditions in day to day life which affects 10- 15% of total population. Gastrointestinal Symptom  Rating Scale (GSRS) is a tool used to measure the  severity and gradation of dyspepsia. Infections,  gastrointestinal motor abnormalities, brain-gut  interaction, visceral hypersensitivity, inflammation,  central neural dysregulation, altered gut flora are  main reasons for gastrointestinal disorders. Common  presentations of gastro intestinal disorders are nausea,  vomiting, heart burn, dyspepsia, pain abdomen,  flatulency, bowel movement alteration (constipation,  diarrhoea) and bleeding per rectum.Homoeopathy  is asystem of medicine which is based on “Similia  Similibus Curentur” and with the combination of  constitutional prescription and law of similars the  normal harmonious health will be maintained in all  the patients.
Keywords: Gastrointestinal disorders; Gastrointes tinal Symptom Rating Scale; Homoeopathy